Entendendo as interações entre povos pesqueiros, manguezal e área protegida: RDS estadual Ponta do Tubarão (RN, Brasil) - Mattos, Patrícia Pereira (2011)
The mangrove ecosystem has a great importance to maintaining marine biodiversity, and to the livelihoods of communities living around it. Despite its importance, many mangrove areas have been extensively cleared and converted to other uses. There are few places where communities can retain their traditional uses of mangrove. A good example of conservation of traditional costumes are the fishing communities of the Sustainable Development Reserve (Reserva de Desenvolvimento Sustentável RDS) Ponta do Tubarão. The creation of the reserve came from the own population, and the devastation of a mangrove area, which would be destined for activity shrimp, was one of the reasons that led the population to ask authorities the establishment of a legally protected area. Thus, this study aimed to investigate the environmental perception of the fishing communities of RDS Ponta do Tubarão with respect to the mangroves in a biological, ecological and social perspective as well as evaluate the influence of the reserve in the mangrove conservation and quality of life. To meet objectives of this study was required the appropriation of some method and approaches of ethnosciences and environmental perception. Data were collected through direct observation, and semi-structured interviews. Through content analysis found that the population has a strong dependence on the mangrove ecosystem, as well as provides a good ecological knowledge of ecosystem functions. It was also found that the reservation has a good performance in the conservation of the mangroves; however, need to outline strategies to conciliate both the biological and cultural conservation.